Enhance the Overseas Market Competitiveness of Chinese Cigarette Brands - Guo, Zhenzhong; Bi, Chuanchen (Technium Social Sciences Journal, 2023)
Enhancing the competitiveness of Chinese cigarette brands on the global stage requires competition with Western tobacco companies. Factors favoring Chinese cigarette products in foreign trade analysis are numerous. To improve the competitiveness of Chinese cigarette brands in the global market, it is essential not only to venture abroad and engage in learning and research but also to have institutional and talent support.